Lekor Enterprise / Mohd Ariff Fahmi M. Amran ... [et al.] - M Amran, Mohd Ariff Fahmi; Konsaga, Dastel; Mimin, Rosalia; Durahim, Adriani; Lanjut, Pauline (2010)
We are starting our own business as partners, and all of us decided to call our business as Lekor Enteprise. Our main activity of business is producing new product which is the Lekor Ayam. The type of ownership of this business is partnership. Each members of this company contribute RM 20000.00 and to sum up this amount, our total of capital is RM 100000.00. The location that we chose for running our business is at Kampung Kionsom, Inanam because to reduce the cost of operation as this location and building is being contributed by the member of this partner. Moreover, this place is near to our major suppliers as well. This business will start on the 1st of January 2010. The members of this business operate this business as the administrative, operational, financial, and marketing aspect and also become the workers to produce the product as well. This is for beginning of our business to reduce the cost of production of the product.